PENGARUH PEMAHAMAN KONSEP PERCAYA DIRI DALAM AL-QUR’AN TERHADAP MASALAH QUARTER-LIFE CRISIS PADA MAHASISWA - Mashdaria Huwaina; Khoironi Khoironi (PARAMUROBI: JURNAL PENDIDIKAN AGAMA ISLAM, 2021)
Quarter-life crisis is a feeling of worry that is present over the uncertainty of the future life, namely around personal, social, family, work relationships, which occurs around the age of twenties. Students are individuals who are affected by the quarter-life crisis because they are in early adulthood or emerging adulthood. The emotional crisis experienced by students in the long term due to accepting the challenge of a quarter-life crisis can cause various negative impacts on life, one of which is stress and depression. Islam in the holy book Al-Qur'an provides several ways to increase individual self-confidence in order to answer the challenges of the quarter-life crisis, namely by recognizing self-concept, positive thinking, belief and action, surrender (Tawakal), gratitude and self-evaluation. (Nur Huda, 2016). This study involved 200 students using quantitative methods and using a Likert scale, namely the concept of self-confidence in the Qur'an (Nur Huda, 2016) and the quarter-life crisis scale (Christine Hassler, 2009). The results showed that the understanding of the concept of self-confidence in the Qur'an proved to have a significant effect on the quarter-life crisis problem for students by 11.2% (p<0.01). The results of the Pearson correlation show a positive score of 0.335 which strengthens the relationship between variables so that the higher the understanding of the concept of self-confidence in the Qur'an, the higher the problem of quarter-life crisis in students.